2013
DOI: 10.1093/ndt/gft281
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of addition of mineralocorticoid receptor antagonist to angiotensin II receptor blocker in patients with diabetic nephropathy: a randomized clinical trial

Abstract: Abstract Background Addition of spironolactone (SPR) to angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs) might provide antiproteinuric effects beyond what is gained by either medication alone. This study was designed to assess the long-term efficacy of SPR/ARB combination in comparison with the standard ACE/ARB regimen in diabetic nephropathy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 41 publications
4
49
0
Order By: Relevance
“…A progressive decline in eGFR was observed in all groups, which is consistent with previous observations [17,18,19]. The proportion of patients that experienced a rise of 30% above baseline in serum creatinine after a median of 34 days was 39.1% [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A progressive decline in eGFR was observed in all groups, which is consistent with previous observations [17,18,19]. The proportion of patients that experienced a rise of 30% above baseline in serum creatinine after a median of 34 days was 39.1% [18].…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of patients that experienced a rise of 30% above baseline in serum creatinine after a median of 34 days was 39.1% [18]. In another study of 136 patients, the eGFR showed a decline from 74.39 to 64.16 mL/min/1.73 m 2 after 12 months of treatment with spironolactone [19]. Our data revealed that the eGFR reduces by about 18 mL/min/1.73 m 2 in patients with 1≤UACR<3.5 g/g creatinine, which is higher than the finding of previous studies however, this reduction seems to be transient and could be restored.…”
Section: Discussionmentioning
confidence: 99%
“…From a total of 236 potentially eligible studies, 220 were excluded because they were not relevant to the study objectives; were reviews, meeting abstracts, case-only studies (ie, a control group [in which control medication or placebo was added to standard AD/RP/AHT treatment] was not included); or contained no detailed, usable data necessary for the meta-analysis. A total of 16 studies 23,28,34,35,[42][43][44][45][46][47][48][49][50][51][52][53] were included in the present metaanalysis and are described in the table (see also Supplemental Tables 1A-3B in the online version 28,34,43,45,47,49,52,53 ; and hyperkalemia, 12 studies (spironolactone, 319; control, 295). 28,34,35,[43][44][45][46]48,49,50,52,53 Effects of the Addition of Spironolactone on Urinary Protein/Albumin Excretion Compared with controls, the addition of spironolactone to standard AD/RP/AHT treatment significantly reduced end-of-treatment 24-hour urinary albumin/protein excretion (MD = -61.48; 95% CI, -96.74 to -26.23; P = 0.0006) (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] There have also been reports that adding spironolactone to standard RP treatment provided added benefit in terms of proteinuria reduction and BP control. 34,35 However, large-scale, prospective clinical studies of the effects of adding spironolactone to standard RP treatment have not yet been conducted in patients with DN, mainly because of the reported hyperkalemia associated with spironolactone use. 36 There has been 1 meta-analysis of the effects of adding an aldosterone antagonist to ACEI/ARB treatment in patients with chronic kidney disease (CKD) 26 ; however, it was conducted in 2008 and thus did not include numerous later studies, and further it was not limited to DN and thus the effects of the addition of spironolactone in patients with DN was not specifically analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were never treated (n=75) or underwent a washout period for at least 2 weeks (n=27). This washout period has been widely used [33][34][35][36] and described to be sufficient to eliminate the effects of previous antihypertensive treatments on physiological parameters [37]. Patients underwent a complete medical history, physical examination, and laboratory analysis to exclude subjects with evidence of severe or secondary hypertension; other concomitant cardiovascular diseases; or respiratory, hepatic, renal, or hematological dysfunction.…”
Section: Subjects and Study Designmentioning
confidence: 99%